What is the solution to the system -2x + y = 6 and y= 2x - 3?
1 answer:
<span>
replace y= 2x - 3 into </span>-2x + y = 6
-2x + 2x - 3 = 6
<span>
- 3 = 6 .....no solutions....
</span>
You might be interested in
Answer:
2.35 x 10^3
Step by Step:
- Rewrite the number in scientific notation.
2.35 x 10^3
Answer:
a6=6
Step-by-step explanation:
V=12
Equation: v=-3(-1-3)
V=-3(-4)
V=12
Answer:
If you're isolating X then it would equal x=1
Answer:
17/100*85= $14.45
Step-by-step explanation:
Divide by 100 and multiply by (100-15) 85 to get the result.